Imazamox Absorption, Translocation, and Metabolism by Cereal Rye (Secale cereale) at Low Temperatures. Issue 2 (9th January 2019) - Ostlie, Michael H.; Shaner, Dale; Bridges, Melissa; Westra, Phillip
Abstract: Cereal rye ( Secale cereale L.) control in wheat ( Triticum aestivum L.) can be difficult with existing selective herbicides. High phenotypic diversity within populations coupled with suboptimal herbicide application conditions leads to varying degrees of control with herbicide treatments. The following research focused on the consequence of low temperature on imazamox fate in S. cereale . A greenhouse study was conducted to determine the number of warm-temperature days required for imazamox to control S. cereale . Absorption, translocation, and metabolism of imazamox was evaluated under warm (22/18C) and cold (4/4C) temperatures to identify changes to the fate of imazamox under different environmental conditions. In greenhouse conditions, more than 5 d of warm temperature following herbicide application was required to achieve 80% S. cereale mortality. Absorption of imazamox was reduced 20% when S. cereale was subjected to cold compared with warm temperatures. Only 10% of applied imazamox was moved from the treated leaf in continuous cool temperatures compared with greater than 60% in warm conditions. In cold conditions, imazamox content increased in all tested plant parts evaluated for the duration of the study, whereas in warm conditions, imazamox concentrations decreased in root and crown tissues after 3 d. Imazamox behavior was affected more by temperature than S. cereale growth stage. Secale cereale metabolism of imazamox was reduced, but not stopped in cold temperatures. After 6 d, only a 10% difference in intact imazamox remained between temperature treatments. In cold temperatures, reduced absorption and translocation, coupled with continued metabolism, allow plants to recover from an otherwise lethal imazamox treatment.